Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was reading through Apostol's Calculus where he has this equality, but I can't figure out how to prove this equality. I would appreciate a hint if you could help. Thank you. $$ [(\sum_{k=1}^{n-1}k)+1]^3-(\sum_{k=1}^{n-1}k)^3=n^3-1^3 $$ Above shown to be incorrect should be: $$ \sum_{k=1}^{n-1}(k+1)^3-(\sum_{k=1}^{n-1}k)^3=n^3-1^3 $$

Perhaps I am wrong in conveying the equation. Let me show you where I get this from. I am trying to obtain the equation to calculate any sum $(1^2+2^2+...+n^2)$ valid for $n\in Z , n\ge1$

We start by showing $3k^2 + 3k + 1 = (k+1)^3 - k^3.$ Taking k = 1, 2, . . . , n-1 we get the n-1 formulas:

$3\bullet1^2 + 3\bullet 1 + 1 = 2^3 - 1^3$
$3\bullet2^2 + 3\bullet 2 + 1 = 3^3 - 2^3$

Now, when we add the formulas we get:

$3[1^2+2^2+. . . + (n-1)^2]+3[1+2+. . . =(n-1)]+(n-1)=n^3-1^3.$

What I don't get is by how adding the right side of the n-1 formulas we obtain the right side of the last equality.

Perhaps I wrote the sums listed above incorrectly.

share|cite|improve this question
Something is wrong here. For example, if $n=3$, then $\sum_{k=1}^{n-1} k = 1+2 = 3$, and the claim is $4^3 - 3^3 = 3^3 - 1^3$. But it doesn't hold. – hardmath Feb 25 '13 at 9:32
You almost certainly mean $$\sum_{k=1}^{n-1} \big(k+1)^3 - \sum_{k=1}^{n-1} k^3 = n^3 - 1.$$ – mrf Feb 25 '13 at 9:34
up vote 3 down vote accepted

I think there was a little problem with parentheses. You may intend $$\sum_{k=1}^{n-1}(k+1)^3 -\sum_{k=1}^{n-1}k^3.$$ If so, it is just a question of expanding out the sums. The first is the sum of the cubes from $2^3$ to $n^3$, and the second is the sum of the cubes from $1^3$ to $(n-1)^3$. Equivalently, it is $$\left(2^3+3^3+4^3+\cdots+(n-1)^3+n^3\right) -\left(1^3+2^3+3^3 +\cdots+(n-1)^3\right).$$ Note the wholesale cancellation when we remove the parentheses. The only things that survive are the $n^3$ from the first part and the $-1^3$ from the second part.

share|cite|improve this answer
Thank you, it somehow went right past me that I had to add 1 to each part of the sum. Thank you for your help. – AlexHeuman Feb 25 '13 at 9:49
You are welcome. Summation notation is nice and compact, but it can interfere with seeing what's really going on. – André Nicolas Feb 25 '13 at 9:51

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.